2008
DOI: 10.21236/ada495522
|View full text |Cite
|
Sign up to set email alerts
|

Natural Attenuation of Perchlorate in Groundwater: Processes, Tools and Monitoring Techniques

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…All of these studies targeted surface waters and their associated stream and lakebed sediments which were relatively rich in organic carbon (OC). There apparently are no conclusive examples of field scale natural attenuation of ClO 4 − in groundwater systems (Lieberman et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these studies targeted surface waters and their associated stream and lakebed sediments which were relatively rich in organic carbon (OC). There apparently are no conclusive examples of field scale natural attenuation of ClO 4 − in groundwater systems (Lieberman et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitous occurrence of ClO 4 − degrading bacteria in the environment has been inferred based on surficial soil and sediment samples (Coates et al ). Meanwhile, microcosm studies (Tipton et al ; Tan et al ; Simon and Weber ; Wilkin et al ; Lieberman et al ), and stream bed profiling at sites near McGregor, Texas (Tan et al ), have shown that ClO 4 − degradation can occur in unamended natural sediments. It has also been inferred that natural attenuation occurs in the anoxic bottom waters of California's Salton Sea because ClO 4 − is absent from the sea but is elevated (about 4 µg/L) in the inlet streams (Holdren et al ).…”
Section: Introductionmentioning
confidence: 99%